Lymphoid stromal reaction in gastrointestinal lymphomas: immunohistochemical study of 14 cases. Issue 7 (July 1987) - Jarry, A; Brousse, N; Souque, A; Barge, J; Molas, G; Potet, F
Abstract : The lymphoid stromal reaction, particularly the T lymphoid reaction, was studied immunohistochemically on cryostat sections in 14 cases of primary gastrointestinal B lymphomas, and compared with the type and distribution of lymphoid cells in three cases of gastric lymphoid hyperplasia. A pronounced T lymphoid reaction, mainly of the T helper phenotype, occurred in both lesions. Most of these T cells bore HLA-DR antigens, but only a few of them had the receptor for interleukin 2. The T lymphoid reaction was observed inside the lymphomas in seven of a total of 14 cases, and around the lymphomas in four of the six cases clinically classified as stage I. Perivascular mucosal and submucosal nodules, entirely composed of T cells, seemed characteristic of gastric lymphoid hyperplasias. A T lymphoid reaction in lymphoid hyperplasias suggests an amplification of the cell mediated immune response; in lymphomas it could represent a host reaction against the lymphomatous infiltrate, therefore favouring a better prognosis.